HASIL BELAJAR BERBICARA SISWA KELAS X-1 SMAN 9 SURABAYA DENGAN MODEL PEMBELAJARAN TAKE AND GIVE - RAHMADANY, WINDA (LATERNE, 2014)
Speaking is one of the four language skills which must be mastered by the students. In fact, however, a lot of students still have some difficulties in speaking because of insufficient grammatical and vocabulary masteryof Deutsch. Therefore, in this research, Take and Give is used to train the students’ speaking skill. Take and Give is done by the students by taking and giving lesson from and to the other students. Teaching each other (Silberman, 2009:23). The research problem is how to learn to speak reproductive outcomes German language class X - 1 model SMAN 9 Surabaya take and give ? . The purpose of this study is to describe the results of learning to speak reproductive class X - 1 SMAN 9 Surabaya models degan take and give . This study is a qualitative research and data analysis of this research is descriptive . Research results obtained from the study before and after the Take and Give learning model , with the following description : From the average value of pre-test results showed 59.00 % and the average post-test 79.60 % . There is an increase in value - average of 20.6 % of the value of pre-test to post - test values ??. Based on these data it can be seen that there is a change for the better results of learning German language speaking skills . From the results of these studies indicate that the Take and Give learning model as a variation model of learning German. Keywords: Models of Learning, speaking skills, models of Take and Give